AGRO TECHNO PRAK ACCOUNTING 5.0: INTEGRATED FARMING ACCOUNTING TECHNOLOGY BUMDES SUCI UNTUK KETAHANAN PANGAN BERKELANJUTAN - Hartanto, Sugeng (Jurnal Ilmiah Akuntansi Peradaban, 2025)
This study examines the fragmentation of agricultural, livestock, and fisheries sector management within Village-Owned Enterprises (BUMDes). This study presents a BUMDes financial management model that integrates across sectors. The research method employed a qualitative approach. Data were obtained through interviews, observation, and documentation. This study began by exploring the experience of BUMDes Suci in managing business units and how it would be implemented using Agroteknopark Accounting 5.0 to produce an integrated accounting model that supports its financial governance. The advantages of the integrated farming model include production cost efficiency, optimization of local resources, increased productivity, and the potential for developing agro-based educational tourism. Keyword: Agrotechnopark, Integrated farming, Food Security